Analysis of the situation and the importance of forestry in the context of sustainable development in Serbia - Nada Mijalović (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
This paper presents the analysis of situation of forests in Serbia. The data to be presented are related to the parameters of the situation of forests in Serbia in the last five years, according to official statistics. The aim was to draw attention to the status of forests in Serbia and the importance and prospects of further development of this important segment of the economy in the context of sustainable agricultural and general development of the state of Serbia. The forests are very important at the global level (primarily as the "lungs" of the planet) in this context should be carried out foreseen measures of care and protection of the forest area. The paper presents the legal documents and Forestry Development Strategy in Serbia. A section is dedicated to analysing the condition of forests in the Serbian Danube as an important region that is part of the Danube basin, which connects several states of the European Union.
Keywords: 330; forestry; sustainable development; biodiversity